Comparing digital image analysis and visual rating of gamma ray induced Kentucky bluegrass (Poa pratensis) mutants - TIWARI, AJAI KUMAR; KUMAR, RAMESH; KUMAR, GUNJEET; KADAM, GANESH B; SAHA, T N; S, GIRISH K (The Indian Journal of Agricultural Sciences, 2015)
Variability was generated in Kentucky bluegrass (Poa pratensis) through gamma-ray irradiation and genotypes were evaluated for their response to low management, induction of dwarfness and other quality attributes. The main objective of this study was to judge the suitability of digital image analysis over visual rating of turf quality and to identify changes in mutants, and correlations among visual rating and digital image analysis were computed. Differences were significant among mutants with respect to hue, brightness and saturation. Significant and positive correlations of hue and DGCI were observed with all the parameters of visual rating. There were non-significant correlations of brightness with quality, brightness with texture, saturation and texture. These relationships were better in DGCI and color (r2=0.123) DGCI and brightness (r2=0.0849); DGCI and hue (r2=0.0772) and DGCI texture (r2=0.0325). Nonlinear relationship was noticed between DGCI and saturation (r2=0.0011).